GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR MAPPING OF DRUG ABUSE USING SPATIAL CORRELATION ANALYSIS IN NORTH SUMATRA PROVINCE - Fitri Isnaini; Narwawi Pramudhiarta (The Republic of Indonesia Defense University, 2020)
Drug abuse is a problem that affects almost every country in the world including Indonesia. In the long term, it has the potential to disrupt competitiveness, weaken national resilience, and can hinder the progress of a nation. North Sumatra is a province that has the highest prevalence of drug abusers in Indonesia, which none of the villages in this Province is free from drug abuse. The North Sumatera Province also has the highest number of drug abusers undergoing rehabilitation at the BNN Rehabilitation Center. The use of geospatial technology can help understand the phenomenon of drug abuse by area or spatial. One of the geospatial technology that commonly uses is the Geographic Information System (GIS). This study aims to show that GIS can be used in mapping drug-prone areas in North Sumatra based on North Sumatran people undergoing drug rehabilitation. The method used is a retrospective based on secondary data and spatial statistics in GIS. The environment prone to drug abuse based on the number of people undergoing drug rehabilitation at the BNN Rehabilitation Center from North Sumatra is divided into 3 zones based on the number of clients distributed in BNN Rehabilitation Center, namely red, yellow and green. Red zone 3 cities/districts namely Deli Serdang, Medan, and Binjai with 9 sub-districts namely Percut Sei Tuan, Medan Amplas, Medan Helvetia, Medan Tembung, Medan Perjuangan, Binjai Utara, Medan Sunggal, Medan Johor, Medan Timur. The yellow area has 25 districts, the green area is 103 districts. In a conclusion, the Geographic Information System (GIS) is a technology that can be used to map drug-prone areas.